2008
DOI: 10.2169/internalmedicine.47.1039
|View full text |Cite
|
Sign up to set email alerts
|

Acute Cytomegalovirus Infection Superimposed on Corticosteroid-Naieve Ulcerative Colitis

Abstract: Most cases of cytomegalovirus (CMV)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…Although our study had a limited number of patients with CD, a higher incidence of CMV in UC compared to CD is consistent with prior reports [8,22]. We found the prevalence of CMV infection in patients with active UC to be lower than previously reported in patients with acute severe colitis (21-38%) [20][21][22][23][24] and steroid-refractory colitis (32-36%) [17,23,25]. This finding may be due to the inclusion of patients with mild to moderate disease activity in our study, unlike previous studies that selected patients with more severe disease.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although our study had a limited number of patients with CD, a higher incidence of CMV in UC compared to CD is consistent with prior reports [8,22]. We found the prevalence of CMV infection in patients with active UC to be lower than previously reported in patients with acute severe colitis (21-38%) [20][21][22][23][24] and steroid-refractory colitis (32-36%) [17,23,25]. This finding may be due to the inclusion of patients with mild to moderate disease activity in our study, unlike previous studies that selected patients with more severe disease.…”
Section: Discussionsupporting
confidence: 92%
“…Initial studies reported CMV inclusion bodies in colectomy specimens with fulminant or steroid-refractory UC [8,15,16]. In addition, treatment with steroids [17], cyclosporine [18], anti-TNF agents [19], and leukapharesis [20] has been associated with an increased risk of CMV infection. However, other studies have challenged the pathogenicity of CMV in active IBD by demonstrating a lack of correlation of CMV and clinical severity of IBD [21].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the diagnosis of concurrent CMV disease in UC patients requires a high degree of certainty. CMV infection can occur regardless of the degree of colonic involvement in UC, i.e., whether the entire colon is involved or only the left side (6,(10)(11)(12)(13)(14)(15). The gold standard for confirming CMV disease of the colon includes endoscopic biopsies taken from the mucosa and ulcer bed.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17][18][19][20][21] In our study CMV was detected in 5 patients who had used only 5-ASA and no immunosuppressant in the past for disease control.…”
Section: Discussionmentioning
confidence: 43%